2016
DOI: 10.1186/s13054-016-1408-0
|View full text |Cite
|
Sign up to set email alerts
|

External validation of a prehospital risk score for critical illness

Abstract: BackgroundIdentification of critically ill patients during prehospital care could facilitate early treatment and aid in the regionalization of critical care. Tools to consistently identify those in the field with or at higher risk of developing critical illness do not exist. We sought to validate a prehospital critical illness risk score that uses objective clinical variables in a contemporary cohort of geographically and temporally distinct prehospital encounters.MethodsWe linked prehospital encounters at 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
0
19
1
Order By: Relevance
“…In the current study, there was a relatively high frequency of critically ill patients of 12%. In previous studies this was 4.5% [8,10]. These studies included not only multiple referral centers of expertise, but also non-referral hospitals, possibly treating patients who were less ill.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the current study, there was a relatively high frequency of critically ill patients of 12%. In previous studies this was 4.5% [8,10]. These studies included not only multiple referral centers of expertise, but also non-referral hospitals, possibly treating patients who were less ill.…”
Section: Discussionmentioning
confidence: 98%
“…This risk stratification tool has been developed in a United States population including non-trauma and non-cardiac arrest patients who were transported to the Emergency Departments of both non-referral hospitals, as well as regional referral centers. Kievlan, et al have validated the model for its use in a similar population in the United States [ 10 ]. This validation study showed an Area Under Receiver Operating Characteristics (AUROC) of 0.73.…”
Section: Introductionmentioning
confidence: 99%
“…We can find multiple studies on the Early Warning Score in the literature, but we opted for the NEWS2 because it is currently the most used in the PhEMS and has a high bibliographical consistency [8, 30].…”
Section: Discussionmentioning
confidence: 99%
“…These scales are composed of simple parameter systems, multiple parameters, or aggregated weighting systems, the latter being the most reliable. 22,30,31 For this study, four triage methods have been selected that can be performed (at least in a theoretical framework) in the context of MCIs at the prehospital level: SI, 32,33 GAP Score, 34,35 RTS, 36,37 and the NEWS2. 20,38 Table 1 shows the parameters that are evaluated in each scale.…”
Section: Triage System Includedmentioning
confidence: 99%